MANAGEMENT OF THE ALAM MAYANG TOURIST ATTRACTION FACILITIES IN THE CITY OF PEKANBARU DURING THE COVID-19 PANDEMIC - Titania Novriza Aurelli M; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The world of tourism is one of the national assets with great potential if tourism resources can be optimized properly. tourism can classified as one of the secondary needs for humans if their primary needs have been reached, to carry out tourism activities humans will pay attention to aspects of facilities, management systems, and a comfort of a tourist attraction. In the city of Pekanbaru has many tourist attractions which one is Alam Mayang tourist park, but for now that park has been limited for public due to the spread of the covid-19 virus so that it makes parties tourism has changed some of management systems to avoid transmission of the virus Covid-19, which are by implementing appropriate health protocols government policy. Therefore, this study purpose to identified the condition of the Alam Mayang tourist attraction facilities, the management's efforts in managing the facilities in the Alam Mayang tourist park as well and to know about obstacles are faced by managers in managing facilities at the Alam Mayang tourist attraction. In this study, the authors using qualitative methods as a procedure for processing data. Data collection techniques used are observation, interviews and documentation of the owner as well as the manager of the tourist attraction, after the interviews with informants, the author's conclude that the facilities at the Alam Mayang tourist attraction has been managed well and the implementation of health protocols has been implemented perfectly , but the flaw is this park has lack of children's playgrounds. Keywords: Management, Facilities, Covid-19 Virus, constraint, Health Protoco